Lemierre’s syndrome in a pediatric patient with otomastoiditis caused by Streptococcus anginosus: A case report (Research, Society and Development, 2024)
Lemierre's syndrome is a rare disease characterized by complications secondary to oropharyngeal infection, including septic thrombophlebitis, with the internal jugular vein (IJV) being the most common site of involvement. It can also lead to septic emboli formation in other locations. First reported in 1936, its incidence has increased in recent years. Treatment includes antibiotic therapy, with no consensus in the literature regarding anticoagulation or surgical intervention, which should be evaluated on a case-by-case basis. The purpose of this report is to highlight the rare presentation of the syndrome in pediatric patients, providing a detailed description of clinical progression, complications, and treatment adopted. Additionally, it aims to contribute to the monitoring of complications in pediatric patients initially diagnosed with common conditions. This paper discusses the clinical case of a 5-year and 5-month-old male pediatric patient initially diagnosed with acute otitis media, progressing to otomastoiditis caused by Streptococcus anginosus. During hospitalization, he developed septic arthritis in the left hip, pleural effusion, IJV thrombosis, and sigmoid sinus thrombosis, characteristic findings of Lemierre's syndrome.